1998
DOI: 10.1002/1529-0131(199801)41:1<48::aid-art7>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Antiinflammatory and immunoregulatory action of methotrexate in the treatment of rheumatoid arthritis: Evidence of increased interleukin-4 and interleukin-10 gene expression demonstrated in vitro by competitive reverse transcriptase-polymerase chain reaction

Abstract: In vitro modulation of the cytokine network by MTX, increasing Th2 cytokines and decreasing Th1 cytokines, could explain its antiinflammatory and immunoregulatory actions in vivo during the treatment of RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
1
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(71 citation statements)
references
References 44 publications
2
67
1
1
Order By: Relevance
“…59 In PBMC stimulated with mitogens and treated with MTX, an increase in IL-4 and IL-10 gene expression was found and correlated with serum levels of these cytokines. 16 In RA patients treated with MTX alone or in combination with etanercept, no significant changes were observed in serum concentration of IL-4 and IL-10. 43 In our study, itolizumab did not have a clear effect on IL-10, as was previously demonstrated in psoriasis patients receiving the antibody as monotherapy.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…59 In PBMC stimulated with mitogens and treated with MTX, an increase in IL-4 and IL-10 gene expression was found and correlated with serum levels of these cytokines. 16 In RA patients treated with MTX alone or in combination with etanercept, no significant changes were observed in serum concentration of IL-4 and IL-10. 43 In our study, itolizumab did not have a clear effect on IL-10, as was previously demonstrated in psoriasis patients receiving the antibody as monotherapy.…”
Section: Discussionmentioning
confidence: 97%
“…53 However, when PBMC from RA patients were stimulated with phytohemagglutinin and treated with MTX, an increase in Th2 cytokines and a decrease in Th1 cytokines was observed. 16 In RA patients treated with MTX, a significant decrease in IL-6, IFN-g 54 and TNF 54,55 levels has also been seen. The same effect was obtained in the cases of IL-6 and TNF in patients treated with a combination of MTX with either etanercept 43 or abatacept.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Data from animal models show that IL-4 ameliorates CIA in DBA/1 mice, and synovial fluid mononuclear cells (SFMC) from RA patients treated with IL-4 in vitro are more resistant to Th1 activation [32]. A number of disease-modifying agents (methotrexate and gold) promote Th2 cells while suppressing Th1 cells [33,34]. In addition, many women experience improvement of their arthritis during pregnancy (reviewed in [35]), and the switch towards a Th2 profile in pregnancy may be at least partially responsible [36].…”
Section: Discussionmentioning
confidence: 99%
“…In autoimmune diseases, MTX is used at low doses (up to 30 mg once weekly) given orally or by intramuscular or subcutaneous injections 7 . It has antiinflammatory and cytokine-modulating properties that are thought to contribute to the beneficial effect of MTX in the treatment of RA and other chronic inflammatory conditions such as psoriasis and psoriatic arthritis 8 . Complications of MTX, which include hematological and hepatic adverse events and less frequently lung or bone marrow toxicities, are well known and may easily be detected by careful monitoring of hematological measurements and renal and hepatic functions 1 .…”
Section: Rheumatologymentioning
confidence: 99%